2012
DOI: 10.1021/jf3013663
|View full text |Cite
|
Sign up to set email alerts
|

Muscadine Grape (Vitis rotundifolia) and Wine Phytochemicals Prevented Obesity-Associated Metabolic Complications in C57BL/6J Mice

Abstract: The objective of this study was to determine the effects of muscadine grape or wine (cv. Noble) phytochemicals on obesity and associated metabolic complications. Muscadine grape or wine phytochemicals were extracted using Amberlite FPX66 resin. Male C57BL/6J mice were given a low-fat diet (LF, 10% kcal fat), high-fat diet (HF, 60% kcal fat), HF + 0.4% muscadine grape phytochemicals (HF+MGP), or HF + 0.4% muscadine wine phytochemicals (HF+MWP) for 15 weeks. At 7 weeks, mice fed HF+MGP had significantly decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 45 publications
4
42
0
1
Order By: Relevance
“…In the past, we have suggested that polyphenolic phytochemicals may be acting via transactivation or antagonism selected nuclear hormone receptors in the liver and other tissues [43,44] It is evident that raspberry phytonutrients and/or their subsequent colonic metabolites are absorbed into the blood stream, and may thus have effects on major metabolic target tissues such as liver and muscle. Recent gene expression studies [25,26], and metabolomic evaluations data support this presumption. For example, a metabolic evaluation of liver tissue shows accumulation of raspberry-related metabolites including methyl glucopyranoside and S-methylmethionine only when whole raspberry products were provided to mice fed a HF diet [45].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In the past, we have suggested that polyphenolic phytochemicals may be acting via transactivation or antagonism selected nuclear hormone receptors in the liver and other tissues [43,44] It is evident that raspberry phytonutrients and/or their subsequent colonic metabolites are absorbed into the blood stream, and may thus have effects on major metabolic target tissues such as liver and muscle. Recent gene expression studies [25,26], and metabolomic evaluations data support this presumption. For example, a metabolic evaluation of liver tissue shows accumulation of raspberry-related metabolites including methyl glucopyranoside and S-methylmethionine only when whole raspberry products were provided to mice fed a HF diet [45].…”
Section: Discussionmentioning
confidence: 95%
“…Ellagic acid appears to be emerging as a phytonutrient that may provide health benefits. For example, recent studies show that the level of EA in fruit extracts produces beneficial effects on metabolic disease symptoms in mice and alters the metabolism of human adipocytes [25,26]. In the GI tract, EA is converted into a family of compounds calls the urolithins [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have documented that adipocyte differentiation and lipid accumulation are associated with the development of obesity. Certain dietary compounds derived from plants are considered to be a prescription for anti-obesity by suppression of adipocyte differentiation and regulation of lipid metabolism in culture cells and animal experiments (22)(23)(24). However, there is little research that shows the effect of dietary compounds on adipogenesis through stimulation of intestinal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…The preparation of a library of 3-methyl-8-(4-(2-(methyl(pyridin-2-yl)amino) ethoxy)phenyl)-1H-purine-2,6(3H,7H)-dione derivatives (11) have been carried out in a tandem nine-step sequence from two important intermediates 3 and 9 as described in Scheme 1. Compound 2 was afforded by treatment 2-chloropyridine (1) and 2-(methylamino)ethanol in a good yield.…”
Section: Chemistrymentioning
confidence: 99%
“…Nowadays, an elevated TG is frequently the most available laboratory marker of intracellular accumulation of lipids [11]. Impaired fasting glucose often is found together with an increase TG level, which can interrupt insulin action by multiple mechanisms and lead to insulin resistance ultimately [12].…”
Section: Introductionmentioning
confidence: 99%